Organ specific mapping of in vivo redox state in control and cigarette smoke-exposed mice using EPR/NMR co-imaging - Caia, George L. (2011)
In vivo mapping of alterations in redox status is important for understanding organ specific pathology and disease. While electron paramagnetic resonance imaging (EPRI) enables spatial mapping of free radicals, it does not provide anatomic visualization of the body. Proton MRI is well suited to provide anatomical visualization. We applied EPR/NMR co-imaging instrumentation to map and monitor the redox state of living mice under normal or oxidative stress conditions induced by secondhand cigarette smoke (SHS) exposure. A hybrid co-imaging instrument, EPRI (1.2 GHz) / proton MRI (16.18 MHz), suitable for whole-body co-imaging of mice was utilized with common magnet and gradients along with dual EPR/NMR resonators that enable co-imaging without sample movement. The metabolism of the nitroxide probe, 3–carbamoyl–proxyl (3-CP), was used to map the redox state of control and SHS-exposed mice. Co-imaging allowed precise 3D mapping of radical distribution and reduction in major organs such as the heart, lungs, liver, bladder and kidneys. Reductive metabolism was markedly decreased in SHS-exposed mice and EPR/NMR co-imaging allowed quantitative assessment of this throughout the body. Thus, in vivo EPR/NMR co-imaging enables in vivo organ specific mapping of free radical metabolism and redox stress and the alterations that occur in the pathogenesis of disease.